Graphic Media E-Learning Teaching Materials to Improve Learning Outcomes - Hari Setyaedhi; Andi Mariono; Alim Sumarno (Jurnal Edutech Undiksha, 2023)
Lecturers do not use graphic media e-learning teaching materials accessed through Unesa Virtual Learning (Vinesa). It causes students to become less interested in learning, causing a decrease in student learning outcomes. This study assesses the feasibility and effectiveness of developing graphic media e-learning teaching materials. This type of research is development research with a quantitative approach. Methods of data collection using tests, observations, interviews, and questionnaires. The instrument used is a questionnaire. The analysis used in this research is descriptive quantitative and t-test. The results of the study are the results of the feasibility of developing e-learning teaching materials for visual media, which are declared valid with very feasible material validation (96%), very feasible learning media (94%), very feasible learning designs (94%), very feasible individual trials ( 94%), very feasible small group trial (94%). The effectiveness results show that there is a difference in n-gain results between the control group and the experimental group. Developing e-learning teaching materials using visual media is feasible and effective enough to improve student learning outcomes. Graphic media e-learning teaching materials make it easier for students to learn.